Prospective acceptance of distinct mobile mental health features in psychiatric patients and mental health professionals. (February 2019) - Hendrikoff, Leonie; Kambeitz-Ilankovic, Lana; Pryss, Rüdiger; Senner, Fanny; Falkai, Peter; Pogarell, Oliver; Hasan, Alkomiet; Peters, Henning
Abstract: Background: Despite numerous mobile health (mHealth) applications available, current impact on mental healthcare is low. Users face overwhelming variety of applications and sensors. Evidence for distinct features' effectiveness is largely lacking. Along with technical feasibility and data security issues, readiness and preferences of patients predetermine engagement and impact of mHealth in psychiatry. Objective: We aimed to assess the prospective attitudes of psychiatric patients and mental health professionals (MHP) towards mHealth applications in general and with regard to distinct features. Methods: We conducted a survey entailing 486 subjects (297 MHP and 189 patients). Results: Professionals and patients indicate both, considerable acceptance and rejection for most features. Marked concerns across groups relate to data security in general. Actimetry and geotracking were considered particularly skeptical. Importantly, most patients prefer to be prompted timely about health status changes. Conclusion: Altogether, evidence indicates substantial support for mHealth features in mental healthcare despite considerable rejection of distinct features. We conclude that tighter collaboration between researchers, developers and clinicians must address matching mHealth-apps to patients' needs. Improved information on potential risks and possibilities associated with mHealth features is strongly indicated in MHP and psychiatric patients in order to reach an appropriately informed decision on individual involvement.